Dosimetric analysis and experimental setup design for in-vivo irradiation with a Plasma Focus device. (February 2019) - Isolan, L.; Sumini, M.; Teodori, F.; Bradley, D.; Jafari, S.; Mariotti, F.; Buontempo, F.
Abstract: Looking at possible clinical applications of the Plasma Focus (PF) technology as medium-low energy extremely fast radiation source, aiming at the treatment of skin cancer pathologies, in vivo experiments on mice are a due step. To properly design the experiments, a dosimetric analysis on a PMMA mouse phantom has been devised and carried out. The dose delivered to the phantom has been evaluated in experiments using Gafchromic films, standard TLD chips and TL glass beads to be able to optimally reconstruct the radiation field produced by the PF at various depths in the phantom. The whole setup has also been analysed with a Monte Carlo model using the MCNP6 code to produce a correlation between the results obtained from the various dosimetric technologies. Abstract : Highlights: A Plasma Focus device is analysed as X-ray source for medical applications. The dosimetry to evaluate the possibility of in-vivo experiments has been setup. A comparison between experimental data and MC simulations with the MCNP6 code has been carried out.